Biogeographical estimates of allergenic pollen transport over regional scales: Common ragweed and Szeged, Hungary as a test case - Makra, László; Matyasovszky, István; Tusnády, Gábor; Wang, Yaqiang; Csépe, Zoltán; Bozóki, Zoltán; Nyúl, László G.; Erostyák, János; Bodnár, Károly; Sümeghy, Zoltán; Vogel, Heike; Pauling, Andreas; et al. (Elsevier, 2016)
Long-distance pollen transport can substantially raise local pollen levels, but their relative con-tribution has not yet been quantified temporally or spatially in ragweed infested regions. Usingcommon ragweed (Ambrosia artemisiifolia) pollen accumulation at a ragweed infested area, Szeged,Hungary as a test case, this study attempted to: (1) identify, using cluster analysis, biogeographicalregions that contribute to long-range transport of ragweed pollen to Szeged; (2) quantify the relative
Keywords: ambrosia pollen transport; backward trajectories